Healthcare experiences of pregnant and postnatal women and healthcare professionals when facing child protection in the perinatal period: A systematic review and Critical Interpretative Synthesis - Backer, Kaat De; Rayment-Jones, Hannah; Lever Taylor, Billie; Bicknell-Morel, Tamsin; Montgomery, Elsa; Sandall, Jane; Easter, Abigail (PLOS ONE, 2024)
Background The perinatal period is known as time of transition and anticipation. For women with social risk factors, child protection services may become involved during the perinatal period and this might complicate their interactions with healthcare providers. Aim To systematically review and synthesise the existing qualitative evidence of healthcare experiences of women and healthcare professionals during the perinatal period while facing child protection involvement. Methods A systematic search of databases (Web of Science, MEDLINE, EMBASE, PsychINFO, CINAHL, ASSIA, MIDIRS, Social Policy and Practice and Global Health) was carried out in January 2023, and updated in February 2024. Quality of studies was assessed using the Critical Appraisal Skills Programme. A Critical Interpretative Synthesis was used alongside the PRISMA reporting guideline. Results A total of 41 studies were included in this qualitative evidence synthesis. We identified three types of healthcare interactions: Relational care, Surveillance and Avoidance. Healthcare interactions can fluctuate between these types, and elements of different types can coexist simultaneously, indicating the complexity and reciprocal nature of healthcare interactions during the perinatal period when child protection processes are at play. Conclusions Our findings provide a novel interpretation of the reciprocal interactions in healthcare encounters when child protection agencies are involved. Trust and transparency are key to facilitate relational care. Secure and appropriate information-sharing between agencies and professionals is required to strengthen healthcare systems. Healthcare professionals should have access to relevant training and supervision in order to confidently yet sensitively safeguard women and babies, while upholding principles of trauma-informed care. In addition, systemic racism in child protection processes exacerbate healthcare inequalities and has to be urgently addressed. Providing a clear framework of mutual expectations between families and healthcare professionals can increase engagement, trust and accountability and advance equity.